Improved conductive silver paste composition and preparation method thereof
By using a composite system of silver-clad copper + graphene oxide + conductive polymer + epoxy resin in the conductive silver paste, it combines aniline, benzaldehyde and pyruvate to prepare conductive small-molecular polymers, and uses oxidants to promote the reaction, the existing conductive silver paste has solved the problem of high cost and unstable performance, and achieved cost-effective and high-performance conductive silver paste.
Patent Information
- Application Number
- CN202510366854.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
The existing conductive silver paste has challenges in terms of cost and performance. The fluctuations in silver prices lead to high production costs, limited silver ore resources, and unstable electrical conductivity, making it difficult to adapt to low-temperature processes such as flexible electronics.
A composite system of silver-clad copper + graphene oxide + conductive polymer + epoxy resin is adopted to prepare conductive small-molecular polymers through reactions of aniline, benzaldehyde and pyruvate, and the reaction and dispersion in the system are promoted through oxidizing agents to improve conductivity and mechanical properties.
It realizes coordinated optimization of conductivity, mechanical properties and process adaptability, reduces production costs, improves conductivity, and is suitable for photovoltaics, flexible electronics and automotive electronics fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of conductive material preparation, and more specifically, to an improved conductive silver paste composition and a preparation method thereof. Background Art
[0002] Electronic paste is a basic electronic functional material, which is widely used in the fields of radio frequency identification, sensors, integrated circuits, solar panels, etc. With the advancement of electronic information technology, more and more new electronic devices are pouring into the market, driving the continuous development of electronic technology products towards high integration, miniaturization, intelligence and precision.
[0003] Conductive pastes such as silver paste and aluminum-silver paste are currently the main research directions for electronic pastes. The main components of commercial conductive silver paste are silver particles and organic solvents, but fluctuations in silver prices significantly increase production costs. At the same time, global silver mine resources are limited, which restricts the sustainable development of the industry. The industry has used silver-coated copper instead of silver materials to prepare conductive pastes, which can reduce silver consumption by more than 50%, but the oxidation problem of copper leads to unstable conductivity, limiting its large-scale application.
[0004] In addition, although pure silver powder has excellent conductivity, it is easy to agglomerate and requires high-temperature sintering, making it difficult to adapt to low-temperature processes such as flexible electronics. Existing conductive silver pastes are mostly imported (such as DuPont and Heraeus). Domestic silver powder has uneven particle size distribution and poor morphology control, resulting in low density of the conductive network and a square resistance generally higher than 15×10 -5 Ω·cm. In addition, the conductive filler graphene oxide is easy to restack due to π-π stacking, has poor dispersibility, and requires a complex modification process.
[0005] Based on the above statements, the present application provides an improved conductive silver paste composition and a preparation method thereof. Summary of the invention
[0006] In order to solve the problems raised in the background technology, the present application provides an improved conductive silver paste composition and a preparation method thereof. In the technical solution of the present invention, the prepared conductive silver paste achieves the coordinated optimization of conductivity, mechanical properties and process adaptability through a composite system of silver-coated copper + graphene oxide + conductive polymer + epoxy resin, and has both high cost performance and high performance, and is suitable for photovoltaics, flexible electronics, automotive electronics and other fields.
[0007] The present application provides an improved conductive silver paste composition and a preparation method thereof, using the following technical solutions: An improved conductive silver paste composition comprises the following raw materials in parts by weight: 60-70 parts of silver-coated copper powder, 12-20 parts of graphene oxide, 0.5-1.5 parts of conductive small molecule polymer, 5-8 parts of modified cellulose nanocrystals, 1-3 parts of oxidant, 8-12 parts of epoxy resin and 5-10 parts of diluent; Among them, the conductive small molecule polymer is obtained by the reaction of aniline, benzaldehyde and pyruvic acid; The modified cellulose nanocrystals are obtained by modifying carboxylated cellulose nanocrystals with dopamine hydrochloride.
[0008] Furthermore, the conductive small molecule polymer is prepared by the following steps: Aniline and benzaldehyde are added to ethanol, and the temperature is raised to 75-85° C. after stirring, and stirring is continued for 5-7 hours. Subsequently, pyruvic acid is added to the system, and the reaction is continued for 20-30 hours to obtain a conductive small molecule polymer.
[0009] Further preferably, the conductive small molecule polymer is prepared by the following steps: Aniline and benzaldehyde are added to ethanol, and the system temperature is raised to 75-85°C after stirring at 30-90 rpm for 10-15 minutes at room temperature, and stirring is continued for 5-7 hours. Subsequently, pyruvic acid is added to the system, and the reaction is continued for 20-30 hours to obtain a conductive small molecule polymer.
[0010] In the above reaction process, the aldehyde group on benzaldehyde is oxidized to a carbonyl group, and the amino group acts as a nucleophile to attack the carbonyl group, resulting in condensation to form an imine intermediate. Subsequently, the carboxylic acid group on pyruvic acid is protonated to attack the empty orbital of the imine nitrogen atom, and undergoes nucleophilic substitution with the nitrogen atom of the imine intermediate to form an amide bond. The formed amide bond is conjugated with the benzene ring and the imine bond through intramolecular cyclization, ultimately generating a closed-ring small molecule containing a conjugated π electron system.
[0011] Furthermore, the usage ratio of aniline, benzaldehyde, pyruvic acid and ethanol is (1.3-1.5) g:(1.5-1.7) g:(1.3-1.4) g:30 mL.
[0012] Furthermore, the modified cellulose nanocrystals are prepared by the following steps: Add carboxylated cellulose nanocrystals into MES buffer, stir for 10-20 minutes, then add EDC and NHS, continue stirring for 1-3 hours, then add dopamine hydrochloride, adjust the pH value of the system to 5-6, continue stirring for 20-30 hours, dialyze and dry to obtain modified cellulose.
[0013] Further preferably, the modified cellulose nanocrystals are prepared by the following steps: Add carboxylated cellulose nanocrystals into MES buffer, stir at 30-90 rpm for 10-20 minutes at room temperature, then add EDC and NHS, continue stirring for 1-3 hours, then add dopamine hydrochloride, use 1 mol / L hydrochloric acid solution to adjust the pH value of the system to 5-6, continue stirring for 20-30 hours, dialyze for 2-3 days, and then freeze-dry the product to obtain modified cellulose.
[0014] In the above reaction process, the carboxyl groups on the carboxylated cellulose nanocrystals are activated using the EDC and NHS system, and then react with the amino groups on dopamine hydrochloride to generate amide bonds. Dopamine hydrochloride is grafted onto the carboxylated cellulose nanocrystals, and catechol groups are introduced to prepare modified cellulose nanocrystals.
[0015] Furthermore, the usage amounts of carboxylated cellulose nanocrystals, MES buffer, EDC, NHS and dopamine hydrochloride are (0.5-1.0) g:50 mL:(0.7-0.8) g:(0.4-0.5) g:(0.6-0.8) g.
[0016] Furthermore, the silver-coated copper powder is prepared by the following steps: A1. The nano copper powder was added to a sulfuric acid solution, stirred for 10-20 minutes, and then the temperature was raised to 35-45 ° C. After ultrasonic treatment, the filtrate was added to a sodium hydroxide solution, the temperature was raised to 50-70 ° C, stirred for 10-20 minutes, filtered, and the filtrate was washed to obtain a pretreated nano copper powder; A2. Add silver nitrate to deionized water, stir, add ammonium citrate, continue stirring to obtain a silver ion complex system; disperse the pretreated nano copper powder in deionized water, add ammonia water and sodium oleate, stir, and then drop the silver ion complex system. After the addition is complete, continue stirring for 20-30 minutes, filter and dry to obtain silver-coated copper powder.
[0017] Further preferably, the silver-coated copper powder is prepared by the following steps: A1. The nano copper powder was added to a 5-20wt% sulfuric acid solution in a mass volume ratio of (3-5) g: 20 mL, stirred at a rate of 30-90 rpm for 10-20 minutes at room temperature, and then the system temperature was raised to 35-45 ° C, ultrasonically treated for 2-4 hours at an ultrasonic frequency of 20-40 KHz, and then filtered, and the filtrate was added to a 5-8wt% sodium hydroxide solution in a mass volume ratio of (3-5) g: 20 mL, the system temperature was raised to 50-70 ° C, stirred at a rate of 30-90 rpm for 10-20 minutes, filtered, and the filtrate was washed with deionized water until the pH value of the washing solution was 7 to obtain a pretreated nano copper powder; A2. Silver nitrate was added to deionized water at a mass volume ratio of 1g:10mL, stirred at a rate of 30-90rpm for 10-15 minutes at room temperature, ammonium citrate was added, and stirring was continued for 10-15 minutes to obtain a silver ion complex system; the pretreated nano-copper powder obtained in step A1 was dispersed in deionized water at a mass volume ratio of 1g:10mL, ammonia and sodium oleate were added, and the system was stirred at a rate of 300-500rpm for 10-15 minutes, and then the silver ion complex system was added dropwise at a rate of 1-3mL / min. After the addition was completed, stirring was continued for 20-30 minutes, filtered, and the filtrate was vacuum dried at 20-30pa and 350-400°C for 40-60 minutes to obtain a silver-coated copper powder.
[0018] Furthermore, in step A2, the mass ratio of silver nitrate to ammonium citrate is 1:(0.1-0.3).
[0019] Furthermore, in step A2, the dosage ratio of the pretreated nano-copper powder, ammonia water, sodium oleate and silver ion complex system is (1-3) g: (3-10) mL: (0.1-0.3) g: (20-30) mL.
[0020] A method for preparing an improved conductive silver paste composition comprises the following steps: The silver-coated copper powder, conductive small molecule polymer, modified cellulose nanocrystal, graphene oxide, epoxy resin and diluent in the formula weight are stirred at a rate of 300-500 rpm at room temperature, and then an oxidant is added, the system temperature is increased to 30-40°C, stirred for 1-3 hours, and then cooled to room temperature to obtain an improved conductive silver paste composition.
[0021] During the above reaction process, the conductive small molecule polymer, graphene oxide and catechol functional groups on the modified cellulose nanocrystals are uniformly dispersed through π-π interactions, and the amide condensation on the conductive small molecule polymer is further promoted through the oxidizing action of the oxidant, thereby increasing the content of the conjugated structure; at the same time, through the use of the oxidant, the oxidation degree of the graphene oxide is further increased, thereby increasing its binding effect with the matrix; the conversion of the catechol groups on the modified cellulose nanocrystals to catechol quinone is promoted, and through the coordination action with the silver-coated copper powder, the dispersion effect of the silver-coated copper powder and other components in the system can be improved, sedimentation can be prevented, and the contact points between the silver-coated copper powder and the conductive matrix can be increased, thereby improving the conductive effect of the conductive silver paste from multiple aspects.
[0022] Furthermore, the oxidant is hydrogen peroxide.
[0023] In summary, this application has the following beneficial effects: In the technical solution of the present invention, the conductive silver paste includes a composite system of silver-coated copper + graphene oxide + conductive small molecule polymer + epoxy resin. By using silver-coated copper powder instead of traditional silver powder raw materials, the preparation cost of the conductive silver paste is reduced; at the same time, aniline, benzaldehyde and pyruvic acid components are used to prepare polyaniline-based conductive small molecule polymers to fill gaps, form continuous conductive paths, improve conductivity, and make up for the defect that the conductivity of the silver-coated copper component is slightly insufficient compared to pure silver powder.
[0024] At the same time, by adding an oxidant component to the modified conductive silver paste composition, the oxidation of the catechol group on the modified cellulose nanocrystal in the system can be promoted, and its complexing effect on the silver-coated copper can be promoted. The oxidation of the conductive small molecule polymer can also be completely promoted. The graphene oxide under the action of the oxidant is in an extended state, and can be distributed on the surface of the graphene oxide in the form of face-to-face interaction and chain entanglement with the conductive small molecule polymer, which inhibits the restacking of the graphene oxide and reduces the π-π stacking distance between the graphene and the polymer, thereby improving the charge transfer performance, and at the same time having better dispersibility in the modified system, and generating more contact points with the silver-coated copper metal.
[0025] In addition, the conductive small molecule polymer, graphene oxide and catechol functional groups on the modified cellulose nanocrystals are uniformly dispersed through π-π interactions. The oxidizing action of the oxidant further promotes the amidation condensation on the conductive small molecule polymer and increases the content of the conjugated structure. At the same time, the use of the oxidant further increases the degree of oxidation of the graphene oxide and increases its binding effect with the matrix. The catechol groups on the modified cellulose nanocrystals are promoted to transform into catechol quinone. Through the coordination action with the silver-coated copper powder, the dispersion effect of the silver-coated copper powder and other components in the system can be improved, sedimentation can be prevented and the contact points between the silver-coated copper powder and the conductive matrix can be increased, thereby improving the conductive effect of the conductive silver paste from multiple aspects, achieving the coordinated optimization of conductivity, mechanical properties and process adaptability, and having both high cost performance and high performance, and being suitable for photovoltaics, flexible electronics, automotive electronics and other fields. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The reagents used in the specific implementation of this application are all analytical grade, and: The diluent used was butyl acetate.
[0028] The epoxy resin used is bisphenol A epoxy resin E-51.
[0029] The graphene oxide used is a single-layer graphene oxide with an average thickness of 0.5-1.2 nm and a diameter of 4-7 μm.
[0030] The carboxylated cellulose nanocrystal fibers used have a diameter of 410 nm, a length of 100-500 nm, and a cellulose type I crystal structure.
[0031] Example 1 An improved conductive silver paste composition comprises the following raw materials in parts by weight: 60 parts of silver-coated copper powder, 12 parts of graphene oxide, 0.5 parts of conductive small molecule polymer, 5 parts of modified cellulose nanocrystals, 1 part of oxidant, 8 parts of epoxy resin and 5 parts of diluent; Wherein, the conductive small molecule polymer is prepared by the following steps: Aniline and benzaldehyde were added to ethanol, and the system temperature was raised to 75°C after stirring at 60 rpm for 15 minutes at room temperature, and stirring was continued for 5 hours. Subsequently, pyruvic acid was added to the system, and the reaction was continued for 20 hours to obtain a conductive small molecule polymer; the dosage ratio of aniline, benzaldehyde, pyruvic acid and ethanol was 1.3g:1.5g:1.3g:30mL.
[0032] The modified cellulose nanocrystals are specifically prepared by the following steps: Add carboxylated cellulose nanocrystals into MES buffer, stir at 60 rpm for 15 minutes at room temperature, then add EDC and NHS, continue stirring for 1 hour, then add dopamine hydrochloride, use 1 mol / L hydrochloric acid solution to adjust the pH value of the system to 5, continue stirring for 20 hours, dialyze for 2 days, and then freeze-dry the product to obtain modified cellulose; the amount of carboxylated cellulose nanocrystals, MES buffer, EDC, NHS and dopamine hydrochloride used is 0.5g:50mL:0.7g:0.4g:0.6g.
[0033] Silver-coated copper powder is specifically prepared by the following steps: A1. The nano-copper powder was added to a 5wt% sulfuric acid solution in a mass volume ratio of 3g: 20mL, stirred at 90rpm for 20 minutes at room temperature, and the system temperature was raised to 35°C, ultrasonically treated for 2 hours at an ultrasonic frequency of 30KHz, and then filtered, and the filtrate was added to a 5wt% sodium hydroxide solution in a mass volume ratio of 3g: 20mL, the system temperature was raised to 50°C, stirred at 30rpm for 10 minutes, filtered, and the filtrate was washed with deionized water until the pH value of the washing solution was 7 to obtain a pretreated nano-copper powder; A2. Silver nitrate was added to deionized water at a mass volume ratio of 1g:10mL, stirred at 90rpm for 15 minutes at room temperature, ammonium citrate was added, and stirring was continued for 15 minutes to obtain a silver ion complex system, and the mass ratio of silver nitrate and ammonium citrate was 1:0.1; the pretreated nano copper powder obtained in step A1 was dispersed in deionized water at a mass volume ratio of 1g:10mL, ammonia and sodium oleate were added, and the system was stirred at 500rpm for 10 minutes, and then the silver ion complex system was added dropwise at a rate of 2mL / min. After the addition was completed, stirring was continued for 30 minutes, filtered, and the filtrate was vacuum dried at 30pa and 400°C for 50 minutes to obtain a silver-coated copper powder; in the process, the amount ratio of the pretreated nano copper powder, ammonia, sodium oleate and silver ion complex system was 1g:3mL:0.1g:20mL.
[0034] A method for preparing an improved conductive silver paste composition comprises the following steps: Silver-coated copper powder, conductive small molecule polymer, modified cellulose nanocrystals, graphene oxide, epoxy resin and diluent in the formula weight were stirred at 500 rpm for 20 minutes at room temperature, and then an oxidant was added, the system temperature was increased to 30°C, and stirring was continued for 2 hours, and then cooled to room temperature to obtain an improved conductive silver paste composition, wherein the oxidant used was 70wt% hydrogen peroxide solution.
[0035] Example 2 An improved conductive silver paste composition comprises the following raw materials in parts by weight: 65 parts of silver-coated copper powder, 16 parts of graphene oxide, 1.0 parts of conductive small molecule polymer, 7 parts of modified cellulose nanocrystals, 2 parts of oxidant, 10 parts of epoxy resin and 7 parts of diluent; Wherein, the conductive small molecule polymer is prepared by the following steps: Aniline and benzaldehyde were added to ethanol, and the system temperature was raised to 80°C after stirring at 60 rpm for 15 minutes at room temperature, and stirring was continued for 6 hours. Subsequently, pyruvic acid was added to the system, and the reaction was continued for 25 hours to obtain a conductive small molecule polymer; the dosage ratio of aniline, benzaldehyde, pyruvic acid and ethanol was 1.4g:1.6g:1.35g:30mL.
[0036] The modified cellulose nanocrystals are specifically prepared by the following steps: Add carboxylated cellulose nanocrystals into MES buffer, stir at 60 rpm for 15 minutes at room temperature, then add EDC and NHS, continue stirring for 2 hours, add dopamine hydrochloride, use 1 mol / L hydrochloric acid solution to adjust the pH value of the system to 5.5, continue stirring for 25 hours, dialyze for 2 days, and then freeze-dry the product to obtain modified cellulose; the amount of carboxylated cellulose nanocrystals, MES buffer, EDC, NHS and dopamine hydrochloride used is 0.8 g: 50 mL: 0.7 g: 0.4 g: 0.7 g.
[0037] Silver-coated copper powder is specifically prepared by the following steps: A1. The nano-copper powder was added to a 10wt% sulfuric acid solution in a mass volume ratio of 4g: 20mL, stirred at 90rpm for 20 minutes at room temperature, and the system temperature was raised to 40°C, ultrasonically treated for 3 hours at an ultrasonic frequency of 30KHz, and then filtered, and the filtrate was added to a 6wt% sodium hydroxide solution in a mass volume ratio of 4g: 20mL, the system temperature was raised to 60°C, stirred at 60rpm for 5 minutes, filtered, and the filtrate was washed with deionized water until the pH value of the washing solution was 7 to obtain a pretreated nano-copper powder; A2. Silver nitrate was added to deionized water at a mass volume ratio of 1g:10mL, stirred at 90rpm for 15 minutes at room temperature, ammonium citrate was added, and stirring was continued for 15 minutes to obtain a silver ion complex system, and the mass ratio of silver nitrate and ammonium citrate was 1:0.2; the pretreated nano copper powder obtained in step A1 was dispersed in deionized water at a mass volume ratio of 1g:10mL, ammonia and sodium oleate were added, and the system was stirred at 500rpm for 15 minutes, and then the silver ion complex system was added dropwise at a rate of 2mL / min. After the addition was completed, stirring was continued for 30 minutes, filtered, and the filtrate was vacuum dried at 30pa and 400°C for 50 minutes to obtain a silver-coated copper powder; in the process, the amount ratio of the pretreated nano copper powder, ammonia, sodium oleate and silver ion complex system was 2g:5mL:0.2g:25mL.
[0038] A method for preparing an improved conductive silver paste composition comprises the following steps: Silver-coated copper powder, conductive small molecule polymer, modified cellulose nanocrystals, graphene oxide, epoxy resin and diluent in the formula weight were stirred at 500 rpm for 20 minutes at room temperature, and then an oxidant was added, the system temperature was raised to 35°C, and stirring was continued for 2 hours, and then cooled to room temperature to obtain an improved conductive silver paste composition, wherein the oxidant used was 70wt% hydrogen peroxide solution.
[0039] Example 3 An improved conductive silver paste composition comprises the following raw materials in parts by weight: 70 parts of silver-coated copper powder, 20 parts of graphene oxide, 1.5 parts of conductive small molecule polymer, 8 parts of modified cellulose nanocrystals, 3 parts of oxidant, 12 parts of epoxy resin and 10 parts of diluent; Wherein, the conductive small molecule polymer is prepared by the following steps: Aniline and benzaldehyde were added to ethanol, and the system temperature was raised to 85°C after stirring at 60 rpm for 15 minutes at room temperature, and stirring was continued for 7 hours. Subsequently, pyruvic acid was added to the system, and the reaction was continued for 30 hours to obtain a conductive small molecule polymer; the dosage ratio of aniline, benzaldehyde, pyruvic acid and ethanol was 1.5g:1.7g:1.4g:30mL.
[0040] The modified cellulose nanocrystals are specifically prepared by the following steps: Add carboxylated cellulose nanocrystals into MES buffer, stir at 60 rpm for 15 minutes at room temperature, then add EDC and NHS, continue stirring for 3 hours, then add dopamine hydrochloride, use 1 mol / L hydrochloric acid solution to adjust the pH value of the system to 6, continue stirring for 30 hours, dialyze for 3 days, and then freeze-dry the product to obtain modified cellulose; the amount of carboxylated cellulose nanocrystals, MES buffer, EDC, NHS and dopamine hydrochloride used is 1.0 g: 50 mL: 0.8 g: 0.5 g: 0.8 g.
[0041] Silver-coated copper powder is specifically prepared by the following steps: A1. The nano-copper powder was added to a 15wt% sulfuric acid solution in a mass volume ratio of 5g: 20mL, stirred at 90rpm for 20 minutes at room temperature, and the system temperature was raised to 45 ° C, ultrasonically treated for 4 hours at an ultrasonic frequency of 30KHz, and then filtered, and the filtrate was added to an 8wt% sodium hydroxide solution in a mass volume ratio of 5g: 20mL, the system temperature was raised to 70 ° C, stirred at 90rpm for 20 minutes, filtered, and the filtrate was washed with deionized water until the pH value of the washing solution was 7 to obtain a pretreated nano-copper powder; A2. Silver nitrate was added to deionized water at a mass volume ratio of 1g:10mL, stirred at 90rpm for 15 minutes at room temperature, ammonium citrate was added, and stirring was continued for 15 minutes to obtain a silver ion complex system, and the mass ratio of silver nitrate and ammonium citrate was 1:0.3; the pretreated nano copper powder obtained in step A1 was dispersed in deionized water at a mass volume ratio of 1g:10mL, ammonia and sodium oleate were added, and the system was stirred at 500rpm for 15 minutes, and then the silver ion complex system was added dropwise at a rate of 2mL / min. After the addition was completed, stirring was continued for 30 minutes, filtered, and the filtrate was vacuum dried at 30pa and 400°C for 50 minutes to obtain a silver-coated copper powder; in the process, the amount ratio of the pretreated nano copper powder, ammonia, sodium oleate and silver ion complex system was 3g:10mL:0.3g:30mL.
[0042] A method for preparing an improved conductive silver paste composition comprises the following steps: Silver-coated copper powder, conductive small molecule polymer, modified cellulose nanocrystals, graphene oxide, epoxy resin and diluent in the formula weight were stirred at 500 rpm for 20 minutes at room temperature, and then an oxidant was added, the system temperature was increased to 40°C, and stirring was continued for 3 hours, and then cooled to room temperature to obtain an improved conductive silver paste composition, wherein the oxidant used was 70wt% hydrogen peroxide solution.
[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that silver-coated copper powder is used instead of modified cellulose nanocrystals. Specifically, an improved conductive silver paste composition comprises the following raw materials in parts by weight: 65 parts of silver-coated copper powder, 12 parts of graphene oxide, 0.5 parts of conductive small molecule polymer, 1 part of oxidant, 8 parts of epoxy resin and 5 parts of diluent.
[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that silver-coated copper powder is used instead of graphene oxide. Specifically, an improved conductive silver paste composition comprises the following raw materials in parts by weight: 72 parts of silver-coated copper powder, 0.5 parts of conductive small molecule polymer, 5 parts of modified cellulose nanocrystals, 1 part of oxidant, 8 parts of epoxy resin and 5 parts of diluent.
[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that silver-coated copper powder is used instead of conductive small molecule polymer. Specifically, an improved conductive silver paste composition comprises the following raw materials in parts by weight: 60.5 parts of silver-coated copper powder, 12 parts of graphene oxide, 5 parts of modified cellulose nanocrystals, 1 part of oxidant, 8 parts of epoxy resin and 5 parts of diluent.
[0046] Comparative Example 4 The difference between this comparative example and Example 1 is that carboxymethyl cellulose nanocrystals are used in this comparative example instead of modified cellulose nanocrystals.
[0047] Comparative Example 5 The difference between this comparative example and Example 1 is that no oxidant is added to the formula of the improved conductive silver paste composition in this comparative example. Specifically, an improved conductive silver paste composition comprises the following raw materials in parts by weight: 60 parts of silver-coated copper powder, 12 parts of graphene oxide, 0.5 parts of conductive small molecule polymer, 5 parts of modified cellulose nanocrystals, 8 parts of epoxy resin and 5 parts of diluent.
[0048] Performance Testing Now, the performance of the improved conductive silver paste compositions prepared in Examples 1-3 and Comparative Examples 1-3 of the present application is tested.
[0049] The improved conductive silver paste compositions in different groups were mixed with the curing agent QNP1 (hexahydrotetramethylphthalic anhydride), the mass ratio of the curing agent to the epoxy resin in the formula was 1:8, and then the system was dispersed at a high speed of 1000 rpm for 1 hour, treated in a vacuum degassing machine for 20 minutes, and then coated on a printed circuit board, cured at 100°C for 100 minutes, and then subjected to resistivity test and stability test. The specific test methods are as follows.
[0050] Resistivity test: Use a four-probe resistance tester to measure the square resistance of the silver paste electrode after curing. Each sample is tested 5 times and the average value is recorded.
[0051] Stability test: Place the sample in a 60℃ / 90%RH environment for 1000 hours, observe the resistivity change, test each sample 5 times in parallel, and record the average value.
[0052] The specific performance test results are shown in Table 1: Table 1 From the results shown in Table 1 above, it can be seen that the comprehensive performance of the improved conductive silver paste composition prepared in Examples 1-3 of the present application is significantly better than the products prepared in Comparative Examples 1-6, that is, within the technical solution defined in the present application, the comprehensive performance of the conductive silver paste prepared is excellent.
[0053] From the results in the comparative example, it can be seen that silver-coated copper replaces pure silver powder, reducing silver consumption by more than 50%. At the same time, a continuous conductive network is formed through graphene oxide and conductive small molecule polymer, and the resistivity is close to that of pure silver paste (8-15×10 -5Ω·cm); conductive small molecule polymer is used as a component of conductive silver paste. The polymer fills the gap between silver particles to make up for the defect of insufficient conductivity of silver-coated copper, reducing the resistivity by 15-20%; an oxidant is used in the preparation process to enhance the coordination effect with silver-coated copper, while graphene oxide stretches, inhibits stacking, improves dispersibility, and promotes the amidation condensation of conductive small molecule polymer, thereby enhancing the interface bonding strength with the substrate and improving stability.
[0054] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0055] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An improved conductive silver paste composition, comprising the following raw materials in parts by weight: 60-70 parts of silver-coated copper powder, 12-20 parts of graphene oxide, 0.5-1.5 parts of conductive small molecule polymer, 5-8 parts of modified cellulose nanocrystals, 1-3 parts of oxidant, 8-12 parts of epoxy resin and 5-10 parts of diluent; in, Conductive small molecule polymers are obtained by the reaction of aniline, benzaldehyde and pyruvic acid; The modified cellulose nanocrystals are obtained by modifying carboxylated cellulose nanocrystals with dopamine hydrochloride.
2. The improved conductive silver paste composition according to claim 1, characterized in that: The conductive small molecule polymer is prepared by the following steps: Aniline and benzaldehyde are added to ethanol, and the temperature is raised to 75-85° C. after stirring, and stirring is continued for 5-7 hours. Subsequently, pyruvic acid is added to the system, and the reaction is continued for 20-30 hours to obtain a conductive small molecule polymer.
3. The improved conductive silver paste composition according to claim 2, characterized in that: The dosage ratio of aniline, benzaldehyde, pyruvic acid and ethanol is (1.3-1.5) g: (1.5-1.7) g: (1.3-1.4) g: 30 mL.
4. The improved conductive silver paste composition according to claim 1, characterized in that: The modified cellulose nanocrystals are specifically prepared by the following steps: Add carboxylated cellulose nanocrystals into MES buffer, stir for 10-20 minutes, then add EDC and NHS, continue stirring for 1-3 hours, then add dopamine hydrochloride, adjust the pH value of the system to 5-6, continue stirring for 20-30 hours, dialyze and dry to obtain modified cellulose.
5. The improved conductive silver paste composition according to claim 4, characterized in that: The usage amounts of carboxylated cellulose nanocrystals, MES buffer, EDC, NHS and dopamine hydrochloride are (0.5-1.0) g:50 mL:(0.7-0.8) g:(0.4-0.5) g:(0.6-0.8) g.
6. The improved conductive silver paste composition according to claim 1, characterized in that: The silver-coated copper powder is specifically prepared by the following steps: A1. The nano copper powder was added to a sulfuric acid solution, stirred for 10-20 minutes, and then the temperature was raised to 35-45 ° C. After ultrasonic treatment, the filtrate was added to a sodium hydroxide solution, the temperature was raised to 50-70 ° C, stirred for 10-20 minutes, filtered, and the filtrate was washed to obtain a pretreated nano copper powder; A2. Add silver nitrate to deionized water, stir, add ammonium citrate, continue stirring to obtain a silver ion complex system; disperse the pretreated nano copper powder in deionized water, add ammonia water and sodium oleate, stir, and then drop the silver ion complex system. After the addition is complete, continue stirring for 20-30 minutes, filter and dry to obtain silver-coated copper powder.
7. The improved conductive silver paste composition according to claim 6, characterized in that: In step A2, the mass ratio of silver nitrate to ammonium citrate is 1:(0.1-0.3).
8. The improved conductive silver paste composition according to claim 6, characterized in that: In step A2, the dosage ratio of the pretreated nano-copper powder, ammonia water, sodium oleate and silver ion complex system is (1-3) g: (3-10) mL: (0.1-0.3) g: (20-30) mL.
9. A method for preparing an improved conductive silver paste composition as claimed in any one of claims 1 to 8, characterized in that: The specific steps include: The silver-coated copper powder, conductive small molecule polymer, modified cellulose nanocrystal, graphene oxide, epoxy resin and diluent in the formula weight are stirred at a rate of 300-500 rpm at room temperature, and then an oxidant is added, the system temperature is increased to 30-40°C, stirred for 1-3 hours, and then cooled to room temperature to obtain an improved conductive silver paste composition.
10. The method for preparing an improved conductive silver paste composition according to claim 9, characterized in that: The oxidant is hydrogen peroxide.
Citation Information
Patent Citations
Electroplating device and method for metal coating powder
CN109763162A
Carbon-coated aluminum foil with good heat-conducting property
CN116314835A
Low-silver-content low-temperature sintering type HJT silver paste for solar cell and preparation method of low-silver-content low-temperature sintering type HJT silver paste
CN116936159A
Photocatalyst nano material and preparation method thereof
CN118204122A
Epoxy resin conductive adhesive doped with conductive nanoparticles as well as preparation method and application of epoxy resin conductive adhesive
CN119119934A
Cited By
Nanometer silver powder filler reinforced conductive paste composition and preparation method thereof
CN121617704A